193 The environment and lupus: impact of inflammation and diet on T cell epigenetics. (April 2019) - Richardson, Bruce C
Abstract : Background: Lupus flares when genetically predisposed people encounter environmental agents that trigger the flares such as UV light and infections which cause oxidative stress, but the mechanisms by which environmental agents induce flares are unclear. Our group has shown that lupus-inducing drugs such as procainamide and hydralazine inhibit DNA methylation in dividing CD4 +T cells, converting normal antigen specific T cells into autoreactive, cytotoxic pro-inflammatory cells that are sufficient to cause lupus in mice, and that similar epigenetically altered T cells are found in patients with active lupus. The mechanism(s) by which environmental agents alter the T cell epigenome to create the pathogenic cells was unclear. The enzyme DNA methyltransferase 1 (Dnmt1) is upregulated as T cells enter mitosis by signals transmitted through the ERK pathway, then binds the replication fork where it copies methylation patterns from the parent strand to the daughter strand by transferring the methyl group from S-adenosylmethionine (SAM) to dC bases in the daughter strand. This suggests that environmental agents which inhibit Dnmt1 upregulation or decrease SAM levels may inhibit T cell DNA methylation to trigger lupus flares. Methods: CD4 +T cells from lupus patients and controls were stimulated with PHA then cultured in custom media with normal or low transmethylation micronutrient levels. Oxidative stress was induced by treating the normal CD4 +T cells with peroxynitrite (ONOO-) prior to culture or injection into SJL mice. Methylation sensitive gene expression (CD70, KIR, and perforin) was measured by RT-PCR and flow cytometry Results: PHA stimulated CD4 +T cells from healthy controls expressed higher levels of CD70, KIR, and perforin mRNA and protein when cultured in media with low transmethylation micronutrient levels relative to cells cultured in complete media. Similar increases were seen in cells cultured in media with low or normal media methionine levels. PHA stimulated CD4 +T cells from lupus patients also overexpressed KIR, CD70 and perforin relative to PHA stimulated T cells from controls when similarly cultured. Treating PHA stimulated normal CD4 +T cells with ONOO- also increased methylation sensitive gene expression in normal CD4 +T cells, and low methionine or folate levels further increased gene expression relative to untreated T cells and T cells cultured in complete tissue culture media. Conclusions: Inflammation and transmethylation micronutrient deficiencies synergize to inhibit T cell DNA methylation, contributing to the onset of lupus flares.: Funding Source(s): Lupus Insight Prize from the Alliance for Lupus Research, the Lupus Research Institute and the Lupus Foundation of America